2016
DOI: 10.1108/mrr-02-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

The value relevance of earnings, cash flows and book values in Egypt

Abstract: Purpose Motivated by the lack of research on the value relevance of accounting information in the emerging markets of Middle Eastern countries, and the unique institutional and accounting setting in Egypt, this paper aims to investigate the relation between capital market and accounting information in the emerging market of Egypt. Specifically, based on Egyptian data, this study examines the value relevance of earnings, cash flows from operations and book values. Design/methodology/approach To examine the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 52 publications
9
36
3
7
Order By: Relevance
“…Relevansi nilai informasi akuntansi dianggap sebagai area dalam riset akuntansi berbasis pasar (Mostafa, 2016). Relevansi nilai mengacu pada kegunaan informasi akuntansi, dan didefinisikan sebagai kemampuan informasi laporan keuangan untuk mempengaruhi harga saham (Francis & Schipper, 1999).…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Relevansi nilai informasi akuntansi dianggap sebagai area dalam riset akuntansi berbasis pasar (Mostafa, 2016). Relevansi nilai mengacu pada kegunaan informasi akuntansi, dan didefinisikan sebagai kemampuan informasi laporan keuangan untuk mempengaruhi harga saham (Francis & Schipper, 1999).…”
Section: Pendahuluanunclassified
“…Ide penelitian ini berasal dari artikel awal Ball & Brown (1968) yang bertujuan untuk menilai apakah informasi akuntansi memberikan informasi tambahan yang bermanfaa atau sinyal bagi investor di luar, atas semua sumber informasi yang tersedia untuk umum (misalnya pengungkapan sukarela manajer atau rekomendasi analis) (Kothari, 2001;Dumontier & Raffournier, 2002). Dikarenakan nilai pasar perusahaan merupakan sebagai nilai sekarang dari perkiraan arus kas bersih masa depan, memeriksa hubungan antara informasi akuntansi (seperti laba dan nilai buku) dan nilai pasar perusahaan dapat menunjukkan bahwa informasi akuntansi dapat memberikan informasi baru tentang jumlah, waktu dan/atau ketidakpastian arus kas masa depan (Mostafa, 2016). Dwimulyani (2010) menyatakan bahwa harga saham yang diperdagangkan di pasar modal akan berubah dengan masuknya informasi yang berupa kabar baik maupun buruk dari keadaan perusahaan tersebut.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Wael Mostafa (2016) conducted a study on the emerging market of Egypt to examine the relation between capital market and accounting information. This study found that both individually earnings and book values significantly explain stock prices; Moreover, earnings have more explanatory power beyond book values for stock prices whereas book values do not.…”
Section: Literature Reviewmentioning
confidence: 99%